Inculcating Values Among Learners in Schools: An Analysis of Global Practices and Approaches - Mugambi, Mercy Muthoni (Journal of Education and Training, 2022)
The paper is based on literature review to understand global approaches for implementation of core values in schools. The paper is organized thematically to ensure progressive coverage. The introduction covers the concept of values and elaborates to present global and national perspectives on implementation of values. Further, values have been categorized into academic, social and civic and the core values for schools identified. Statement of the problem shows a gap in the development of values nationally as reflected by incidences of social, economic and psychological, crimes, among them; violence, rape, defilement, incest, child abuse, spouse abuse, femicide, suicide, intolerance and integrity issues of corruption. In addition studies show minimum implementation of values even within the carrier subjects. Requirements for successful implementation of values have been discussed capturing; proper planning, training that is ongoing and specific and, necessary administrative/ organizational arrangements for the integration, interpersonal forms of communication for close contact with implementers, school consultations and guidance, modeling by teachers ,a conducive school environment and adoption of an interdisciplinary approach. Further, the paper has explored approaches that can be used to implement values in the school; direct, integrated, holistic, pedagogical, hidden curriculum, peer to peer, moral reasoning and action learning approach. In addition benefits of value based education and theoretical framework emphasizing the change theory as a comprehensive description and illustration of how and why a desired change is expected to happen in a particular context have been discussed. The paper concludes that, a whole school approach, backed by effective and efficient administrative leadership is crucial for implementation of values. Recommendations propose; strengthening of home and school partnership, community service programmes, continuous reinforcement of values, ongoing teacher development and development of a healthy relationship between, learners, teachers and parents.